CARRYING CAPACITY OF SATTLEMENT BASED ON DISASTER PRONE AREAS - Baiq Harly Widayanti; Osy Insiani (Universitas Negeri Medan, 2021)
The research aims to assess potential locations that can be developed as settlement areas by observing the area's topographical factors as well as the potential for disaster-affected areas. This research used a quantitative qualitative descriptive method with overlay method between existing land use map, topography map with location map affected by flood disaster, volcano eruption, forest fire, avalanche and tsunami. The results of this study was 20,112 ha (24.93%) is a potential area of settlements. Carrying capacity value for the settlements for all districts is above 1 (one) so that all districts have a possibility to develop settlement areas. The development of the settlement area is preferred in the Gangga because the value of the carrying capacity reaches 71.63, while the development of settlements is limited in Bayan and Kayangan. For settlements that have been developed in hazardous areas, the handling is a restriction and prohibition for new developments in disaster-prone areas and relocation in settlement areas in areas with insecurity levels high.Keywords: carrying capacity, disaster, prone-area, risk, settlementsTujuan penelitian ini adalah untuk mengkaji lokasi potensial yang dapat dikembangkan sebagai kawasan permukiman dengan memperhatikan faktor topografi kawasan serta potensi kawasan terdampak bencana. Penelitian ini menggunakan metode penelitian deskriptif kuantitatif dengan metode overlay antara peta penggunaan lahan eksisting, peta topografi kawasan dengan peta lokasi yang terdampak bencana banjir, erupsi gunungapi, kebakaran hutan, longsor dan tsunami. Hasil dari penelitian ini terdapat 20.112 ha (24,93%) wilayah merupakan kawasan potensial permukiman. Nilai daya dukung lahan permukiman untuk semua kecamatan berada di atas 1 (satu) sehingga masih dapat menampung penduduk untuk bermukim. Pengembangan kawasan permukiman diarahkan terutama pada Kecamatan Gangga karena nilai daya dukung permukiman mencapai 71,63, sedangkan yang perlu dibatasi pengembangan permukiman pada Kecamatan Bayan dan Kecamatan Kayangan. Untuk kawasan permukiman yang telah terbangun pada kawasan rawan bencana arahan penanganannya berupa pembatasan dan pelarangan untuk pembangunan baru dan relokasi pada kawasan permukiman yang berada di kawasan dengan tingkat kerawanan tinggi. Kata kunci: bencana, daerah rawan, daya dukung, permukiman, risiko